KRITIK SOSIAL DALAM SERIAL TELEVISI RUSIA ЛУЧШЕ, ЧЕМ ЛЮДИ (LEBIH BAIK DARIPADA MANUSIA) KARYA ANDREY JUNKOVSKY - Rahayu, Tri; Widyastuti, Thera (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
This study aims to analyze social criticism in the Russian television series Лучше, Чем Люди (Better than Us) by Andrey Junkovsky. With a dystophia theme, this study focusing on criticism of human dependence on robotic technology. The data used in this study is a cut scene which is then analyzed by a descriptive analytical method with a semiotic theory by Roland Barthes. The research was conducted by looking at the meaning of denotations and connotations in the Russian television series Лучше, Чем Люди. This study argues that there are 11 scenes that depict human dependence on robotic technology. This is the social criticism in series Лучше, Чем Люди by Andrey Junkovsky.